Autism spectrum disorder in young patients with congenital central hypoventilation syndrome: role of the autonomic nervous system dysfunction - Dudoignon, Benjamin; Maruani, Anna; Delorme, Richard; Patout, Maxime; Fefeu, Mylene; Ellul, Pierre; Bokov, Plamen; Delclaux, Christophe (Orphanet journal of rare diseases, 2024)
Background Congenital central hypoventilation syndrome (CCHS) is a rare condition characterized by alveolar hypoventilation and autonomic nervous system (ANS) dysfunction requiring long-term ventilation. CCHS could constitute a risk factor of autism spectrum disorder (ASD) due to birth injury related to respiratory failure, which remains to be determined. ANS dysfunction has also been described in ASD and there are indications for altered contribution of ANS-central nervous system interaction in processing of social information; thus, CCHS could be a risk factor for ASD based on pathophysiological background also. Our study aimed to determine the prevalence of ASD among CCHS patients, identify risk factors, and explore the relationship between the ANS, evaluated by heart rate variability indices, and adaptative functioning. Results Our retrospective study, based on the analysis of records of a French national center of patients with CCHS under 20 years of age, determined that the prevalence of ASD (diagnosed by a psychiatrist, following the criteria of DSM-4 or DSM-5) was 6/69 patients, 8.7% (95% confidence interval: 3.3–18.0%). In a case (CCHS with ASD, n = 6) – control (CCHS without ASD, n = 12) study with matching on sex, longer neonatal hospitalization stay and glycemic dysfunction were associated with ASD. Adaptative functioning was assessed using Vineland Adaptative behavioral scales (VABS) and heart rate variability indices (including daytime RMSSD as an index of parasympathetic modulation) were obtained from ECG Holter performed the same day. In 19 young subjects with CCHS who had both ECG Holter and VABS, significant positive correlations were observed between RMSSD and three of four sub-domains of the VABS (communication: R = 0.50, p = 0.028; daily living skills: R = 0.60, p = 0.006; socialization: R = 0.52, p = 0.021). Conclusion Our study suggests a high prevalence of ASD in patients with CCHS. Glycemic dysfunction and longer initial hospitalization stays were associated with ASD development. A defect in parasympathetic modulation was associated with worse adaptative functioning.